Maternal deaths as a challenge for obstetric care in times of COVID-19 in Brazil - Raphael Mendonça Guimarães; Marcelo Rasga Moreira (Instituto Materno Infantil de Pernambuco, 2024)
Abstract Objectives: to describe the effects of the Covid-19 pandemic on maternal mortality in Brazil in 2021. Methods: it is an exploratory study with description of the excess maternal mortality in Brazil for 2021, considering different scenarios: (i) 2015-2019 linear trend; (ii) 2020 observed number of deaths; (iii) 2015-2019 linear trend corrected for general mortality excess; (iv) 2020 observed number of deaths corrected for general mortality excess. Results: compared to the trend of the previous five years, the year 2021 showed an excess mortality of 39% (n=3030). The maternal mortality ratio for 2021 drastically exceeded the SDG target for this indicator, reaching approximately 110 maternal deaths per 100,000 live births. In any scenario described, there will be excess maternal mortality in 2021 higher than general mortality and higher than level presented in 2020. Analysis stratified by region demonstrates subnational heterogeneity. Conclusion: Covid-19 pandemic had a considerable impact on maternal health, not only by leading to increased deaths but also by increasing social health inequality. The year 2021 was the most critical period of the pandemic regarding the magnitude of mortality. Barriers to accessing and using essential health services are challenging to achieving health-related Sustainable Development Goals.